2015
DOI: 10.1155/2015/750637
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Myopia

Abstract: Myopia affected approximately 1.6 billion people worldwide in 2000, and it is expected to increase to 2.5 billion by 2020. Although optical problems can be corrected by optics or surgical procedures, normal myopia and high myopia are still an unsolved medical problem. They frequently predispose people who have them to suffer from other eye pathologies: retinal detachment, glaucoma, macular hemorrhage, cataracts, and so on being one of the main causes of visual deterioration and blindness. Genetic and environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 117 publications
(123 reference statements)
4
73
0
6
Order By: Relevance
“…According to research needs, some scholars have carried out myopia research on the eyes of animals such as tree shrews [9,10], chickens [11], mice [12], rats [13], and guinea pigs [14]. Studies have confirmed that form deprivation (FD) in young animals leads to abnormal growth of the eye axis and the formation of obvious myopia [15,16]. Guinea pigs are widely used in the current research on myopia since the eyeball structure and emmetropization mechanism are similar to those of human myopia.…”
Section: Introductionmentioning
confidence: 99%
“…According to research needs, some scholars have carried out myopia research on the eyes of animals such as tree shrews [9,10], chickens [11], mice [12], rats [13], and guinea pigs [14]. Studies have confirmed that form deprivation (FD) in young animals leads to abnormal growth of the eye axis and the formation of obvious myopia [15,16]. Guinea pigs are widely used in the current research on myopia since the eyeball structure and emmetropization mechanism are similar to those of human myopia.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Studies have also demonstrated that intravitreal injection of NOS inhibitors prevented the transient vision-induced increases in choroidal thickness and inhibits myopia recovery in response to normal vision. 32,33 The results showed that daily topical bendazol can slow myopia progression and downregulate HIF-1a expression in young rabbits, presumably linked to the interaction between NO and HIF-1a. Avascular sclera and the outer retina obtain oxygen and nutrients from the choroid, which has an abundant blood flow and they are susceptible to hypoxia and ischaemia; therefore we chose to investigate the changes of HIF-1a expression in the retina and the sclera.…”
Section: Discussionmentioning
confidence: 96%
“…Desjarlais et al (2019) found has-miR-152-3p in the choroid was overexpressed in an oxygen-induced retinopathy mouse model. Since evidence suggested oxidative stress may help explain the altered regulatory pathways in myopia (Francisco et al 2015), further studies are required to explore the function of has-miR-518d-3p and has-miR-152-3p in myopia development.…”
Section: Discussionmentioning
confidence: 99%